Characterisation of SCMs using the R3 test for low carbon cements. - Koufany, Imane; Redondo-Soto, Cinthya; Cuesta-García, Ana María; Santacruz-Cruz, María Isabel; Rodríguez-Ruiz, María Dolores; García-Aranda, Miguel Ángel; Gómez-de-la-Torre, María de los Ángeles (My University, 2024)
The cement industry is working to reduce its environmental impact by replacing clinker with supplementary cementitious materials (SCMs), including pozzolanic materials. This study examines three types of pozzolanic materials: calcined Spanish clays, natural pozzolans, and fly ash. Fifteen materials were analyzed for their kaolinite and amorphous content. We evaluated the pozzolanic activity of these SCMs using the R³ test (measuring heat released and combined water) and the Strength Activity Index (SAI). The R³ test effectively determined pozzolanicity, showing a strong correlation with kaolinite and amorphous content. However, absolute values of heat and combined water varied across materials. For example, clays with over 50% kaolinite released 700-500 J/g of heat, while fly ash with about 70% amorphous content released 200-250 J/g. SAI results and their limitations for SCM classification will also be presented and correlated with pozzolanicity findings.
Keywords: Cemento - Industria; Calorimetría; Cemento - Aspectos ambientales; Cement; R3 Test; Calorimetry; SAI Test; Supplementary cementitious materials (SCMs)